Case Report : Penatalaksanaan Holistik pada Laki – Laki Usia 20 Tahun dengan Bronkitis Akut Berbasis Pengabdian Masyarakat - Fely Syah Imara Siregar; Tischa Rahayu Fonna (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Acute bronchitis, a common respiratory infection, is a significant medical problem, especially among adults, characterized by the sudden onset of a persistent cough, with or without sputum production. Symptoms are self-limiting, usually mild, and resolve spontaneously within 1 to 3 weeks. Current epidemiological data in Indonesia for bronchitis are not recorded with certainty. Still, the incidence of acute respiratory infections with symptoms similar to acute bronchitis is recorded as the highest in Papua at 10.5%, and in Jakarta itself only recorded at 2.7%. This case study discusses a 20-year-old man with complaints of cough with phlegm for 1 week before coming to the health center with thin, white sputum that worsens with activity and exposure to air pollution. Complaints are accompanied by fever and headache. The patient is a light smoker and lives with the patient's brother, who has similar complaints and is also an active smoker in a house with minimal ventilation in a polluted environment due to street dust. Physical examination of the thorax found coarse rhonchi in both lung fields, which led to the diagnosis of acute bronchitis. Based on this case, it was found that the importance of complete and comprehensive treatment of acute bronchitis in men is expected to be a guide to promote treatment and prevention in cases of acute bronchitis.